2018
DOI: 10.1016/j.jcta.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The classification of tensor categories of two-colored noncrossing partitions

Abstract: Our basic objects are partitions of finite sets of points into disjoint subsets. We investigate sets of partitions which are closed under taking tensor products, composition and involution, and which contain certain base partitions. These so called categories of partitions are exactly the tensor categories being used in the theory of Banica and Speicher's orthogonal easy quantum groups. In our approach, we additionally allow a coloring of the points. This serves as the basis for the introduction of unitary eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(93 citation statements)
references
References 18 publications
1
91
0
Order By: Relevance
“…Orthogonal easy quantum groups have been defined for the first time in [BS09] and they have been generalized in [TW18] and [TW17] to unitary easy quantum groups. This section is aimed for readers familiar with easy quantum groups and we refer to the references above for more details.…”
Section: Generalization To Easy Quantum Groupsmentioning
confidence: 99%
“…Orthogonal easy quantum groups have been defined for the first time in [BS09] and they have been generalized in [TW18] and [TW17] to unitary easy quantum groups. This section is aimed for readers familiar with easy quantum groups and we refer to the references above for more details.…”
Section: Generalization To Easy Quantum Groupsmentioning
confidence: 99%
“…For a more detailed introduction to two-colored partitions and their categories, confer [TW17a], and, more specifically for this article, for a treatment of twocolored partitions with neutral blocks, including more examples and illustrations, see [MW18].…”
Section: Reminder On Two-colored Partitions and Their Categoriesmentioning
confidence: 99%
“…Banica and Speicher showed that categories of onecolored partitions correspond to certain quantum subgroups of Wang's ([Wan95]) free orthogonal quantum group O + n , namely the orthogonal easy quantum groups (see[BS09],[Web16] and[Web17a]). Categories of two-colored partitions are in bijection with so-called unitary easy quantum groups (cf [TW17a]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper can be divided into two parts. The first one being purely combinatorial is a contribution to the classification of categories of two-colored partitions, by which it extends the work [TW18]. The second part applies the results on the theory of compact matrix quantum groups using techniques developed in [TW17].…”
Section: Introductionmentioning
confidence: 97%